Succinate/IL-1β Signaling Axis Promotes the Inflammatory Progression of Endothelial and Exacerbates Atherosclerosis - Xu, Jingwen; Zheng, Yabing; Zhao, Yaqing; Zhang, Yujiao; Li, Huilin; Zhang, An; Wang, Xuehan; Wang, Weizong; Hou, Yinglong; Wang, Jiangrong (Frontiers in Immunology, 2022)
Inflammation is an important driver of atherosclerosis. Succinate is a newly extracellular inflammatory alarm released by activated macrophages. Succinate is able to be sensed by succinate receptor 1 (Sucnr1) and then transferred to effector cells. Whether succinate being capable of facilitating the inflammatory response in atherosclerosis is worth exploring. In this study, we firstly found that arterial serum of CHD patients contained significantly higher succinate and IL-1β than HC subjects, and succinate was positively correlated with IL-1β. As demonstrated by the in vitro study, succinate/Hif-1α/IL-1β signal axis existed and significantly facilitated the inflammatory program in HUVECs. Under the co-culture, activated macrophages released succinate, which would be transferred to HUVECs via Sucnr1 and then activate Hif-1α to produce a greater amount of IL-1β. Likewise, the aortic sinus’s inflammatory phenotype was found to be more significant within Apoe-/- mice that were injected with succinate. Furthermore, Sucnr1 inhibitor (NF-56-EJ40) could significantly interrupt succinate/IL-1β signal in HUVECs and macrophages. As revealed by this study, glycolytic metabolism following the release of succinate could be found in atherosclerotic pathology, and succinate would drive succinate/IL-1β signal dependent of Sucnr1 and then exacerbate inflammatory responses. Sucnr1 might be a novel target for cutting off the transduction of succinate signal to prevent the inflammation of atherosclerosis.